Analisis perbedaan aliran harian dan muka air harian terhadap data debit menggunakan two-way anova dengan mendukung penerapan sistem manajemen Mutu ISO 9001:2015 - Hardiyanti, Ari Vera; Pulansari, Farida (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research analyzes differences in daily flow and water level using Two-Way ANOVA in the context of ISO 9001:2015. The study was conducted to evaluate significant differences in data during January-March and their impact on continuous improvement. Flow and water level data showed a normal distribution, reflecting stability, but the homogeneity test results revealed significant variations. Tukey's post hoc test showed significant differences between January-February and February-March, but not between January-March. These variations indicate the need to evaluate causal factors, such as weather patterns or operational instability. The research recommends standardizing procedures to maintain consistency of operational processes. Improved monitoring systems are also needed to ensure data reliability. Regular training for staff is an additional solution to reduce variability and support quality. This step is expected to strengthen the implementation of the principles of ISO 9001:2015.